2020
DOI: 10.3390/fermentation6040102
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Beer: An Overview of Health Benefits and Recent Developments

Abstract: Since time immemorial, ginger has been widely used as a food spice, providing aromatic odor and pungent taste, and as a medicinal plant, with various therapeutic effects such as antioxidant, anti-inflammatory, and analgesic, among others. It has long been an integral constituent of most herbal medicines in Africa, China and India. Its medicinal properties are largely attributed to its outstanding amount of phenolics which include gingerols, paradols, zingerones, and many others. With consumer preference gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 109 publications
0
17
0
1
Order By: Relevance
“…It is interesting to note that, on the fifth day after commencing fermentation, the control fermentation (BAB) showed lower pH values compared to the treated fermentation (HS). The decline in pH could be ascribed to release of organic acids by yeast during fermentation (Adadi & Kanwugu, 2020; Adadi, Kovaleva, Glukhareva, Shatunova, & Petrov, 2017; Nutakor et al., 2020). HS beer fermentation showed slower decline in pH values within fifth day of fermentation which may be attribute to acids from HS, namely, hibiscus acid, succinic acid, oxalic acid (Martínez et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that, on the fifth day after commencing fermentation, the control fermentation (BAB) showed lower pH values compared to the treated fermentation (HS). The decline in pH could be ascribed to release of organic acids by yeast during fermentation (Adadi & Kanwugu, 2020; Adadi, Kovaleva, Glukhareva, Shatunova, & Petrov, 2017; Nutakor et al., 2020). HS beer fermentation showed slower decline in pH values within fifth day of fermentation which may be attribute to acids from HS, namely, hibiscus acid, succinic acid, oxalic acid (Martínez et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to the purity law, beer is brewed from a mixture of malts, hops, water and yeast. However, in an attempt to create new sorts of beers, other additives (i.e., spices) are added (Adadi & Kanwugu, 2020; Adadi, Kovaleva, Glukhareva, Shatunova, & Petrov, 2017; Nutakor, Essiedu, Adadai, & Kanwugu , 2020). Beer is overwhelmed with amino acids, vitamins, minerals, carbohydrate and polyphenols (Leitao et al., 2011); thus, moderate drinking may substantially improve health conditions of consumers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analysis of essential oils from white ginger extract and red ginger extract revealed that the main components were linalool, borneol, zingiberene, and zingerone. 12 Zingerone, which is contained in high quantities in ginger extract, contributes to providing various pharmacological effects, namely: as an antidiabetic, antidiarrheal, antivirus, antioxidant, and anti -inflammatory agent. 13,14 Zingiberene, which is the second largest amount of essential oil contained in ginger extract, contributes to various pharmacological effects, namely as an anti-hyperlipidemia and anti-inflammatory agent.…”
Section: Resultsmentioning
confidence: 99%
“…Brewers influenced the sensory quality, stability, and health safety of beers in the ancient brewing system by adding medicinal and edible plants that contained active principles responsible for bitterness or flavouring of the beer. In the 21 st century, a resilient approach is being put in place to encourage the consumption of natural or less processed products, including herbal beers, depending on the region [13] . Indeed, due to their antimicrobial activities against certain pathogens, antioxidative properties, and essential oils, plants have been used as beer additives for flavouring and, more importantly, as food preservatives since ancient times [14] .…”
Section: Introductionmentioning
confidence: 99%